1999
DOI: 10.1021/ac990117+
|View full text |Cite
|
Sign up to set email alerts
|

Nanoliter-Volume 1H NMR Detection Using Periodic Stopped-Flow Capillary Electrophoresis

Abstract: Recent advances in the analysis of nanoliter volumes using 1H NMR microcoils have led to the application of microcoils as detectors for capillary electrophoresis (CE). Custom NMR probes consisting of 1-mm-long solenoidal microcoils are fabricated from 50-micron diameter wire wrapped around capillaries to create nanoliter-volume detection cells. For geometries in which the capillary and static magnetic field are not parallel, the electrophoretic current induces a magnetic field gradient which degrades the spect… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
121
0

Year Published

2000
2000
2011
2011

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 116 publications
(122 citation statements)
references
References 33 publications
1
121
0
Order By: Relevance
“…As most of the native amino acids absorb only slightly or not at all ultraviolet light (UV), different detection approaches were used in combination with the CZE and MEKC separation techniques. UV and fluorescence or laser-induced fluorescence (LIF) detection after a suitable precolumn, postcolumn and on-column derivatization with a UV chromophore [8][9][10][11][12][13][14] and fluorophore [7,[15][16][17][18], respectively, direct UV detection at a very low wavelength [19,20], indirect UV detection [21], electrochemical detection [22,23], mass spectrometry [24,25], and some other detection techniques [26,27] were applied to the analyses of amino acids.…”
Section: Introductionmentioning
confidence: 99%
“…As most of the native amino acids absorb only slightly or not at all ultraviolet light (UV), different detection approaches were used in combination with the CZE and MEKC separation techniques. UV and fluorescence or laser-induced fluorescence (LIF) detection after a suitable precolumn, postcolumn and on-column derivatization with a UV chromophore [8][9][10][11][12][13][14] and fluorophore [7,[15][16][17][18], respectively, direct UV detection at a very low wavelength [19,20], indirect UV detection [21], electrochemical detection [22,23], mass spectrometry [24,25], and some other detection techniques [26,27] were applied to the analyses of amino acids.…”
Section: Introductionmentioning
confidence: 99%
“…The major drawback is still the low capacity of standard CE systems, equipped with UV detectors to yield specific information about sample components. CE coupled with other detectors, such as CE-MS [132,151], CE-inductively coupled plasma (ICP)-MS [152,153], CE-NMR [154,155], CE-FTIR [156], CERaman [157,158], and CE-X-ray [159] is capable to provide more structural elucidation. At present, however, only the on-line MS technique has a sufficient detection sensitivity for structural identification.…”
Section: Discussionmentioning
confidence: 99%
“…For example, on-line NMR detection was first shown to work with CE by Wu et al [94,95] and has been used for the analysis of peptides [96]. More recently, Sweedler and co-workers [97] have shown that NMR detection can be used in stop-flow CE analysis and achieve nanogram sensitivity for arginine and triethylamine (TEA), 7 ng (330 pmole; 31 mM), and 9 ng (88 pmole; 11 mM), respectively. Although other methods are more sensitive (i.e., LIF), using NMR detection structural information can be obtained.…”
Section: Unconventional Ce Detection Methodsmentioning
confidence: 99%